A cross-sectional, case-control study of intracranial arterial wall thickness and complete blood count measures in sickle cell disease - Yuan, Shuai (Br J Haematol, 2020)
In individuals with sickle cell disease (SCD), tissue oxygen delivery is sensitively dependent on abilities to increase cerebral blood flow and volume through relaxation of smooth muscle lining intracranial arteries. We hypothesized that anemia extent and/or circulating markers of inflammation lead to concentric macrovascular arterial wall thickening, visible on intracranial vessel wall imaging (VWI) MRI. Adult and pediatric SCD (n=69; age=19.9±8.6 years) and age- and sex-matched control (n=38; age =22.2±8.9 years) participants underwent 3 Tesla VWI; two raters measured basilar and bilateral supraclinoid internal carotid artery (ICA) wall thickness independently. Mean wall thickness was compared with demographic, cerebrovascular, and hematological variables (significance: two-sided p<0.05). Mean vessel wall thickness was elevated (p<0.001) in SCD (1.07±0.19 mm) compared to control (0.97±0.07 mm) participants after controlling for age and sex. Vessel wall thickness was higher in participants on chronic transfusion therapy (p=0.013). No significant relationship between vessel wall thickness and (i) flow velocity, (ii) hematocrit, (iii) white blood cell count, or (iv) platelet count was observed, however trends (p<0.10) for wall thickness increasing with decreasing hematocrit and increasing white blood cell count were noted. Findings are discussed in the context of how anemia and circulating inflammatory markers may impact arterial wall morphology.